2022
DOI: 10.1002/smll.202107284
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Redox Electrochemistry of MOF‐Derived fcc‐NiCo@GC Polyhedron as an Advanced Electrode Material for Boosting Specific Energy of the Supercapattery

Abstract: Metal organic frameworks (MOFs), which constitute a new class of porous organic–inorganic hybrid materials, have gained considerable attention in the fields of electrochemical energy storage and conversion devices owing to their open topological structures, large surface areas, tunable morphologies, and extreme redox activity. A synthesis protocol that comprises coprecipitation followed by controlled calcination processes to design a battery‐type electrode is used. This electrode consists of three‐dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 65 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…At a specific current of 1.0 A g –1 , the specific capacities of 1-ox and 2-ox are up to 833.2 and 828.3 C g –1 , about 10 times of those of 1 and 2 . The specific capacities of 1-ox and 2-ox are superior to those of most of the previously reported supercapatteries. The GCD curves at a specific current of 1 A g –1 of 1-ox′ and 2-ox′ as well as iodine were also recorded and displayed in Figure S15e and S15f. The specific capacities at 1 A g –1 are 657.5, 627.0, and 174.2 C g –1 for 1-ox′ , 2-ox′ , and iodine, respectively.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…At a specific current of 1.0 A g –1 , the specific capacities of 1-ox and 2-ox are up to 833.2 and 828.3 C g –1 , about 10 times of those of 1 and 2 . The specific capacities of 1-ox and 2-ox are superior to those of most of the previously reported supercapatteries. The GCD curves at a specific current of 1 A g –1 of 1-ox′ and 2-ox′ as well as iodine were also recorded and displayed in Figure S15e and S15f. The specific capacities at 1 A g –1 are 657.5, 627.0, and 174.2 C g –1 for 1-ox′ , 2-ox′ , and iodine, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Growing demands for powerful and sustainable energy sources continuously promote the development of alternative renewable energy source devices. , A supercapattery, as an important electrochemical energy storage device, consists of two different electrode materials, a battery-type electrode and a supercapacitor-type electrode . Therefore, it may produce higher power delivery capability than common batteries and higher energy-storage capability than conventional capacitors. An enticing approach to optimizing the supercapattery is to choose novel electrode materials. The essential characteristics for an ideal electrode material are a high density of redox-active sites and a good accessibility of ions to each redox-active site.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been made to develop novel energy storage devices . Supercapatteries consisting of a battery-type electrode and a supercapacitor-type electrode possess both important characteristics of batteries and capacitors with high energy-storage and high power delivery capabilities. The performances of supercapatteries mainly depend on adequate electrode materials. In this respect, more battery-type positrode materials have been explored such as metal hydroxides, oxides, and sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, ZIF-based films with 0.3 to 0.5 nm gap sizes have recently been consolidated with oxide-based dynamic materials as a viable sieving layer, advancing progress for exceptionally specific gas sensing. , In recent times, MOFs and their composites are rapidly gaining consideration in various materials science fields, such as gas storage, sensors, supercapacitors, batteries, catalysis, and so forth. This could be attributed to their advantageous characteristics that include high porosity, the facile synthetic tunability of various inorganic metal atoms or ions and organic ligands, a large specific surface area, open cavities, and so forth. It has been shown that MOF-driven metal oxides (MOS) nanostructures are suitable to analyze the low concentration of various gas molecules. For instance, the ZIF-8 derived ZnO nanocatalysts prepared by Xia et al showed appropriate sensing performance toward the detection of acetone (0.1 to 2 ppm) .…”
Section: Introductionmentioning
confidence: 99%